PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN DIMEDIASI OLEH KEPUASAN PELANGGAN PADA PENGGUNA MARKET PLACE SHOPEE - Candra Afreza; Wiyadi Wiyadi (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the effect of service quality and trust on customer loyalty mediated by customer satisfaction in Shopee market place users. In this study, the population used is the entire shopee user community. The sampling technique in this study was non probability sampling. The sampling technique used is purposive sampling. The number of samples in this study were 260 respondents. The data collection method used in this study was to distribute questionnaires via google form. The questionnaire was made using a Likert scale format and processed using the Partial Least Square (PLS) analysis tool. This analysis process was carried out using the Smart PLS 3.2 application. The results showed that service quality has no effect on customer loyalty. Trust has a positive and significant influence on customer loyalty. Service quality has a positive and significant influence on customer satisfaction. Trust has a positive and significant influence on customer satisfaction. Customer satisfaction has a positive and significant effect on customer loyalty. Customer satisfaction can mediate the effect of service quality on customer loyalty. Customer satisfaction can mediate the effect of trust on customer loyalty. Keywords: Trust, Service Quality, Customer Loyalty, Customer Satisfaction